New U-series and coupled ESR/U-series dating of Hulu Cave, a key Homo erectus site in China - Qingfeng Shao; Christophe Falguères; Yunping Huang; Salah Abdessadok; Wenbo Bao; Jianing He; Xi Chen; Xianglin Zhou; Xinrui Jin; Guilan Hu; Bassam Ghaleb; Yingfei Zhang; et al. (Quaternary Science Reviews, 2026)

Terrestrial laser scanning point cloud-based simulation of microtopographic loess slope in water erosion - Wenli Rao; Yangyang Zhou; Qingfeng Zhang; Jiaqi Qu; Fanfei Ren (Geomorphology, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Alterations in the soil micro-food web and phosphorus availability in tropical agroforestry systems - Guangfan Zhou; Qingfeng Wang; Zhaobo Fan; Ying Shan; Guiliang Wang; Miao Chen; Yukun Zou; Qinfen Li; Jinchuang Wang (Applied Soil Ecology, 2026)

Short-term nitric oxide gaseous treatment of post-rigor pork: Multidimensional impacts on meat quality, protein oxidation and proteolysis, and microstructure - Jiaye Zhu; Yongmao Ye; Liangyu Zhang; Haoyang Ma; Xinnuo Zhou; Yu Qi; Qingfeng Ge; Mangang Wu; Hai Yu; Rui Liu (Food Chemistry, 2026)

Experimental investigation of a residential multi-split air-conditioning system with partial heat recovery for domestic hot water - Yujue Zhou; Baolong Wang; Wenxing Shi; Zhigang Wang; Qingfeng Bie; Xianguo Jiang; Zhanwen Zhao (Energy and Buildings, 2026)

Lymph node-targeted H2S-self-releasing multifunctional prodrug for the dual remodeling of immunological and redox homeostasis in autoimmune uveitis - Qinjin Dai; Yuelan Wu; Wenbo Geng; Mengna Li; Wanyun Zhang; Yuxian Lai; Pei Zhang; Xiaoyue Zhang; Chunjiang Zhou; Yinuo Wang; Qingfeng Cao; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Mechanistic insights into chromium immobilization and uptake inhibition in lettuce mediated by endophyte-loaded biochar - Qizhen Liu; Jie Yuan; Ziyan Fan; Ancao Pan; Qingfeng Zhang; Rui Zhou; Nazish Jabeen Abbasi; Chao Yu; Ying Feng (Journal of Hazardous Materials, 2026)

Fish-gill-inspired hierarchical membranes with charge-repulsion-mediated ion-selective nanostructures for enhanced desalination performance - Yingxue Zhang; Wei Sun; Haoyu Jiang; Qiuxuan Zhou; Najun Li; Qingfeng Xu; Hua Li; Dongyun Chen; Jianmei Lu (Chemical Engineering Journal, 2026)

Variations in soil nutrients and functional microbe abundances govern GHGs emissions under different rice rotation regimes - Zheng Zhao; Xiangyang Gui; Jinxi He; Zhimin Sha; Qingfeng Wang; Deping Zhou; Changbin Chu; Shuhang Wu (Agricultural Systems, 2026)

Exosomal Protein Biomarkers for Predicting Early Neurological Deterioration Following Intravenous Thrombolysis in Acute Ischemic Stroke - Jiamin Li; Zixin Wang; Yingnan Zhou; Xinyi Wang; Qi Kong; Jiameng Li; Boyi Yuan; Yun Chen; Wan Wang; Jiapeng Zhao; Jinming Sheng; Haiping Zhao; et al. (Translational Stroke Research, 2026)

Highly efficient recovery of gold by selective sulfide reduction from chlorine leachate - Qingfeng Ling; Shiwei Zhou; Bo Li; Yonggang Wei; Hua Wang (Journal of Cleaner Production, 2026)

Seasonal characteristics of atmospheric oxidizing capacity at environmental background area in North China from long-term field observations of O3, HONO and HCHO - Shuangshuang Ge; Zhiqiang Ma; Hailiang Zhang; Hanyu Zhang; Weiwei Pu; Yulu Qiu; Jinlong Hou; Chao Liu; Yucong Guo; Fan Dong; Di He; Liyan Zhou; et al. (Atmospheric Environment, 2026)

Gaussian Function Affine Transformation Model: A Bridge Between Laboratory and Downhole Logging NMR in Shale Oil Reservoirs - Junjie Wang; Pengfei Zhang; Weizheng Gao; Wenbiao Li; Nengwu Zhou; Guohui Chen; Qingfeng Li; Chao Liu; Shuangfang Lu (Natural Resources Research, 2026)

Differential organ-specific toxicity profiling of BDE-209 and its derivative DBDPE in zebrafish - Jiaqi Zhou; Changqing Zhang; Zihan Li; Chao Fan; Qingfeng Zhai; Meihua Zhang (Environmental Pollution, 2026)

Keratan sulfate revisited: UPLC–MS/MS-based quantitative profiling reveals structural heterogeneity and deficiency in ocular pathologies - Xinping Wang; Han Zhou; Xi Liang; Yue Li; Shimei Shen; Yuxin Li; Qingfeng Niu; Bi Ning Zhang; Shuying Xu; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2026)

Discovering the causal mechanism of day-night extreme heat driven by 2D and 3D urban landscape changes: a case study of Wuhan, China - Yingqiang Zhong; Shaochun Li; Xinmeng Zhou; Xun Liang; Qingfeng Guan (Sustainable Cities and Society, 2026)

Impedance inversion of high-frequency Chirp sub-bottom profiles constrained by borehole data - Linqing Zhang; Xishuang Li; Lejun Liu; Xiangmei Meng; Qingjie Zhou; Kai Liu; Qingfeng Hua; Jingqiang Wang (Marine Georesources & Geotechnology, 2026)

Influence of target spectrum selection in wind spectrum fitting on fatigue damage assessment accuracy for wind turbine blades - Jiantao Liu; Yibing Liu; Chao Zhou; Qingfeng Gao; Haolin Yin (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

A carbon-negative aerogel with superior CO₂ capture, flame retardancy, and strength based on a cellulose/MOF three-dimensional network - Huinan Wang; Lingling Zhu; Wenjie Xia; Mingdi Kang; Qianqian Zhou; Weichen Shi; Xinyi Xiang; Qingfeng Sun; Yingying Li (Chemical Engineering Journal, 2025)

Evidence for vertical transmission of avian reovirus in chickens - Li Chen; Lijuan Yin; Li Li; Zhiqiang Wu; Jialin Yang; Shenghua Yang; Xuesong Li; Qingfeng Zhou; Zhanxin Wang; Wencheng Lin (Veterinary Microbiology, 2025)

CoCA: Spatial cooperative simulation and future prediction of “land-population-economy” in urban agglomerations - Chenglong Zeng; Yao Yao; Jiayao Liu; Zhenhui Sun; Kun Zhou; Dongsheng Chen; Qingfeng Guan (Landscape and Urban Planning, 2025)

Downregulated miR-199a-3p in Preeclamptic Placenta-derived Exosomes from Cord Blood Hinders VEGF-induced Fetal Glomerular Dysplasia Through Inhibiting Akt1(S473) Phosphorylation via Targeting PHLPP2 - Xiaotong Jiang; Mengqi Gu; Yu Xie; Yuchen Li; Qingfeng Lv; Pengzheng Chen; Die Jing; Yu Zhou; Xietong Wang; Lei Li (Stem Cell Reviews and Reports, 2025)

Integrated Analysis of Phenotypic and Hepatic Transcriptomic Profiles Reveals Enhanced Cold Tolerance in Triploid Crucian Carp - Suifei Tao; Zexun Zhou; Shandong Chen; Jialin Cui; Yude Wang; Kaikun Luo; Wei Liu; Qingfeng Liu; Wuhui Li; Shaojun Liu (Fishes, 2025)
Cold stress poses a critical threat to fish survival by triggering metabolic dysfunction, oxidative damage, immune suppression, and apoptosis. However, hybrid polyploid fish triploid crucian carp (3nRCR, 3n = 150) demonstrate superior stress tolerance. In this study, we investigated the cold adaptation mechanisms in different ploidy cyprinid fishes: triploid crucian carp compared to its diploid improved red crucian carp (Carassius auratus red var., RCC, 2n = 100, ♀) and improved allotetraploid (4nAT, 4n = 200, ♂) progenitors. Under controlled cooling, 3nRCR lost equilibrium at a significantly lower temperature (3.2 °C) than RCC (4.0 °C) and 4nAT (4.5 °C), confirming its superior enhanced cold resistance. Histological examination revealed minimal tissue damage in 3nRCR, characterized by reduced gill inflammation and cellular apoptosis. Transcriptomics revealed triploid-specific molecular strategies: 3nRCR uniquely activated retinol metabolism and metabolic rewiring (arginine/proline metabolism, oxidative phosphorylation). Notably, in the immune-related NLR signaling pathway, both nlrp1 and nlrp3 (key inflammasome components) were significantly downregulated in 3nRCR (p

Electrospinning-mist polymerized antibacterial and super-hydrophilic nanofiber membrane for efficient dust filtration and enhanced comfort in mines - Gang Zhou; Liwei Jiang; Bo Wei; Pengjin Liu; Jiafa Du; Tingting Fan; Song Xin; Rulin Liu; Qingfeng Xu; Seeram Ramakrishna (Chemical Engineering Journal, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

Evaluation of slag and tannery sludge based geopolymer after thermal exposure: Properties, phase transformation and Cr leaching behavior - Jialin Chen; Jingfei Zhou; Shoukai Chen; Haibo Shi; Qingfeng Hu; Yingdong Tang (Journal of Cleaner Production, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

An Ocular Exposure Prediction for Topical Atropine in Human Using Physiologically Based Pharmacokinetic Modeling - Aole Zheng; Tian Han; Fengjiao Bu; Qingfeng He; Jianmin Shang; Paul Chi Lui Ho; Xiaoqiang Xiang; Xingtao Zhou; Taomin Huang (The AAPS Journal, 2025)

Identifying low-to-middle-income residents’ secondary activity patterns using smart card data - Ziyan Zhao; Meihan Jin; Mei-Po Kawn; Qingfeng Zhou; Yongxi Gong; Yu Liu (Travel Behaviour and Society, 2025)

Association of PM2.5-bound multiple metals co-exposure with early cardiovascular damage: A panel study in young adults combining metabolomics - Junjie Chen; Qingfeng Zhou; Yingrong Wang; Yuting Wu; Miao Li; Haotian Wang; Guoying Zheng; Yulan Hao; Xiangke Cao; Wenqi Yang; Lei Zhang; Qian Wang (Environmental Pollution, 2025)

Variation of Wyrtki Jets Influenced by Indo-Pacific Ocean–Atmosphere Interactions - Qingfeng Feng; Jiajie Zhou; Guoqing Han; Juncheng Xie (Journal of Marine Science and Engineering, 2025)
As important components of the equatorial current system in the Indian Ocean, Wyrtki jets (WJs) play a significant role in distributing heat and matter in the East and West Indian Oceans. By dividing the El Niño-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) events into several phases, we find that the spring branch exhibits positive (negative) anomalies during the El Niño (La Niña) decaying phase, while the fall branch exhibits negative (positive) anomalies during the El Niño (La Niña) developing phase. The spring and fall branches are characterized by negative (positive) anomalies under the influence of positive (negative) dipole events, and these anomalies are particularly pronounced during fall. This study systematically analyzes the characteristics of WJs under the interactions between the Indo-Pacific ocean and the atmosphere, based on the phase-locking characteristics of ENSO, and reveals the regulatory mechanisms underlying their different response patterns.

Mechanism of photoluminescence properties of lyocell fibers changing with crystallinity - Xiaoping Lei; Qingfeng Wu; Xiangxi Zhang; Qing Zhou; Lingmin Yi (Carbohydrate Polymers, 2025)

Microbial community and dynamic changes of extracellular polymeric substances in relation to plastisphere of disposable surgical masks in natural aquatic environment - Ling Zhang; Yuxin Zhou; Zixian Zhu; Feifei Yan; Luxi Tan; Chunyan Wei; Zihao Wang; Qingfeng Chen; Ying Zhang (Journal of Oceanology and Limnology, 2025)

Effect of different Agrobacterium rhizogenes strains on hairy root induction and analysis of metabolites in Physalis peruviana L. - Yijia Zhong; Zhie Zhou; Zhongping Yin; Lu Zhang; Qingfeng Zhang; Yihai Xie; Jiguang Chen (Journal of Plant Physiology, 2025)

Different ploidy-level hybrids derived from female common carp × male topmouth culter - Conghui Yang; Chenghua Dai; Qiong Liu; Yating Zhu; Xuexue Huang; Xiaowei Xu; Yi Zhou; Shi Wang; Qingfeng Liu; Shaojun Liu (Aquaculture, 2025)

MOFs meets wood: Renewable, self-supporting carbon-based composites for electromagnetic interference shielding with heat-resistant and electrothermal management - Yujun Rong; Xin Zhou; Shaohua Jiang; Wenkai Zhu; Hanwei Wang; Baokang Dang; Qingfeng Sun; Xiaofan Ma (Chemical Engineering Journal, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

Distribution of oil mist particles and air quality improvement in the working area of the cutting workshop - Yuming Zhang; Yang Yang; Qingfeng Cao; Yi Wang; Jia-Ning Fan; Hu Chen; Xin Wang; Fei Wang; Yu Zhou; Mengfan Quan (Journal of Hazardous Materials, 2024)

Anti-enterovirus 71 activity of native fucosylated chondroitin sulfates and their derivatives - Qingfeng Niu; Han Zhou; Xiaoyao Ma; Yuanyuan Jiang; Chanjuan Liu; Wei Wang; Guangli Yu; Guoyun Li (Carbohydrate Polymers, 2024)

Stomatin-like protein 2 promotes cell proliferation and survival under 5-Fluorouracil stress in hepatocellular carcinoma - Xiaoqi Li; Yahui Zheng; Kangkang Yu; Sen Hou; Huxiao Cui; Ruiqi Yin; Yu Zhou; Qingfeng Sun; Jubo Zhang; Chong Huang (Molecular Biology Reports, 2024)

Anti-tumor and anti-metastasis of water-soluble sulfated β-glucan derivatives from Saccharomyces cerevisiae - Jia Li; Mengmeng Zheng; Zhe Wang; Yang Liu; Qingfeng Niu; Han Zhou; Depeng Wang; Jike Song; Hongsheng Bi; Bin Guo; Guangli Yu; Chao Cai (Carbohydrate Polymers, 2024)

Coupling low phosphorus fertilization with straw amendment highlights large crop productivity and reduced N2O emission in vegetable production - Zheng Zhao; Shuhang Wu; Haitao Zhu; Deping Zhou; Changbin Chu; Qingfeng Wang; Sixin Xu; Shumei Cai; Deshan Zhang (Applied Soil Ecology, 2024)

Characterization of shale oil and water micro-occurrence based on a novel method for fluid identification by NMR T2 spectrum - Junjie Wang; Shuangfang Lu; Pengfei Zhang; Qingfeng Li; Yajie Yin; Wenbiao Li; Nengwu Zhou; Guohui Chen; Yangjian Yi; Chenxi Wu (Fuel, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Distribution and transformation of potentially toxic elements in cracks under coal mining disturbance in farmland - Yin Lu; Xin Xiao; Yan Liang; Junchi Li; Chunying Guo; Lili Xu; Qingfeng Liu; Yu Xiao; Shiyuan Zhou (Environmental Geochemistry and Health, 2024)

Coupled ESR and U-series dating of the northernmost evidence of Gigantopithecus from Jianshi Longgudong site, China - Fei Han; Jean-Jacques Bahain; Qingfeng Shao; Pierre Voinchet; Fangfang Tang; Mi Zhou; Manchen Huang; Gongming Yin (Quaternary Geochronology, 2024)

Ferroptosis is involved in trophoblast cells cytotoxicity induced by black phosphorus nanoparticles - Ruolan You; Yaming Mu; Jiaqi Zhou; Chunying Wang; Zhenya Fang; Yu Liu; Shiyu Liu; Qingfeng Zhai; Changqing Zhang (Toxicology, 2024)

A study of different agricultural practices over a dozen years: Influence on soil CO2 fixation rates and soil autotrophic microbial communities - Qingfeng Wang; Changbin Chu; Zheng Zhao; Deping Zhou; Shuhang Wu (Soil and Tillage Research, 2024)

A repertoire of single nucleotide polymorphisms (SNPs) of major fecundity BMPR1B gene among 75 sheep breeds worldwide - Chunna Cao; Qian Zhou; Yuxin Kang; Zhanerke Akhatayeva; Peiyao Liu; Yuheng Bai; Ran Li; Yu Jiang; Qingfeng Zhang; Xianyong Lan; Chuanying Pan (Theriogenology, 2024)

Extracellular vesicles in plant-microbe interactions: Recent advances and future directions - Junsong Zhang; Liying Pan; Wenjie Xu; Hongchao Yang; Fuge He; Jianfeng Ma; Linlin Bai; Qingchen Zhang; Qingfeng Zhou; Hang Gao (Plant Science, 2024)

Extraction of lithium and phosphorus from amblygonite using calcium sulfate roasting and water leaching - Qingfeng Zhou; Xiangdong Ma; Xunhui Xiong (Hydrometallurgy, 2024)

Quantification of allochthonous and autochthonous organic carbon in large and shallow Lake Wuliangsu based on distribution patterns and δ13C signatures of n-alkanes - Qingfeng Zhao; Aifeng Zhou; Yuxin He (Organic Geochemistry, 2024)

Design and optimization of liquid nitrogen precooling BOG re-liquefaction process for LNG ships - Lesheng Liu; Ting Guo; Xianglei Kong; Jiubing Shen; Qingfeng Jiang; Yanyan Zhou; Xing Tong (International Journal of Refrigeration, 2024)

Diversification of faunal exploitation strategy and human-climate interaction in Southern China and Southeast Asia during the last deglaciation - Yongxiu Lu; Feng Gao; Yiren Wang; Minmin Ma; Aifeng Zhou; Ruiliang Liu; Hiroki Kikuchi; Lele Ren; Qingfeng Shao; Lin Chen; Yongxiang Xu; Haoran Li; et al. (Quaternary Science Reviews, 2023)

The hind information: Exploring the impact of physical damage on mask microbial composition in the aquatic environment - Hu Wang; Zixian Zhu; Ling Zhang; Xiaohui Liu; Weihong Sun; Feifei Yan; Yuxin Zhou; Zhi Wang; Xiaofeng Wang; Chunyan Wei; Jie Lai; Qingfeng Chen; et al. (Environmental Research, 2023)

Zinc/carbon nanomaterials inhibit antibiotic resistance genes by affecting quorum sensing and microbial community in cattle manure production - Lizhi Li; Weikun Guan; Yihao Fan; Qin He; Dongsheng Guo; An Yuan; Qingfeng Xing; Yang Wang; Ziqin Ma; Jian Ni; Jia Chen; Qilong Zhou; et al. (Bioresource Technology, 2023)

Optimization and control strategy of BOG re-liquefaction process for LNG vessels - Ting Guo; Lesheng Liu; Jiubing Shen; Qingfeng Jiang; Sichen Wu; Yanyan Zhou; Yi Liu (International Journal of Refrigeration, 2023)

Enhanced enzyme thermostability of a family I.3 lipase LipSR1 by T118A mutation at the calcium-binding site - Shijie Jiang; Zhengfu Zhou; Jiahui Han; Qingfeng Fan; Zhijian Long; Jin Wang (Biotechnology Letters, 2023)

Effect of high hydrostatic pressure on the edible quality, health and safety attributes of plant-based foods represented by cereals and legumes: a review - Yangyue Ding; Qingfeng Ban; Yue Wu; Yuxue Sun; Zhihao Zhou; Qi Wang; Jianjun Cheng; Hang Xiao (Critical Reviews in Food Science and Nutrition, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Variation in Sunshine Duration and Related Aerosol Influences at Shangdianzi GAW Station, China: 1958–2021 - Weijun Quan; Zhiqiang Ma; Ziming Li; Xiaolan Li; Yingruo Li; Xiangao Xia; Huaigang Zhou; Hujia Zhao; Zhenfa Wang; Weiwei Pu; Fan Dong; Di He; et al. (Journal of Meteorological Research, 2023)

Seismic event classification based on a two-step convolutional neural network - Long Yue; Junhao Qu; Shaohui Zhou; Bao’an Qu; Yanwei Zhang; Qingfeng Xu (Journal of Seismology, 2023)

Purification technology of oil mist in industrial buildings: A review - Yang Yang; Hu Chen; Qingfeng Cao; Mengdan Qiao; Yi Wang; Jia-Ning Fan; Chunhui Yang; Bo Pan; Xin Wang; Fei Wang; Wenchao Ju; Yu Zhou (Building and Environment, 2023)

Association of biomass fuel use with the risk of vision impairment among Chinese older adults: a cohort study - Ying Zhou; Minzhi Xu; Pan Ke; Hongkun Di; Yong Gan; Jing Feng; Xin Meng; Cheng Su; Qingfeng Tian; Zuxun Lu (Environmental Science and Pollution Research, 2023)

AIFM1 variants associated with auditory neuropathy spectrum disorder cause apoptosis due to impaired apoptosis-inducing factor dimerization - Yue Qiu; Hongyang Wang; Huaye Pan; Jing Guan; Lei Yan; Mingjie Fan; Hui Zhou; Xuanhao Zhou; Kaiwen Wu; Zexiao Jia; Qianqian Zhuang; Zhaoying Lei; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Sulfonate-modified calixarene-based porous organic polymers for electrostatic enhancement and efficient rapid removal of cationic dyes in water - Lechen Tian; Shiyuan Zhou; Jiaojiao Zhao; Qingfeng Xu; Najun Li; Dongyun Chen; Hua Li; Jinghui He; Jianmei Lu (Journal of Hazardous Materials, 2023)

Mechanochemical incorporation of magnesium in iron-based composite surface for efficient hydrogenation of carbon dioxide to light olefin - Haipeng Chen; Ningning Ma; Chenwei Wang; Chenlei Liu; Xiaoyu Zhang; Weiwei Yuan; Wenqiang Li; Shixue Zhou; Qingfeng Yang; Xun Feng (Fuel, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Mechanism of molecules crosstalk and the critical role of jasmonic acid on triterpenoid synthesis in Cyclocarya Paliurus cells under Aspergillus niger elicitor - Meng Wang; Daobang Tang; Qiongqiong Xiong; Jiguang Chen; Xiaoxiang Xu; Qingfeng Zhang; Jingen Li; Xiangju Zhou; Zhongping Yin (Journal of Plant Biochemistry and Biotechnology, 2022)

Sediment Waves on the Western Slope of the Chukchi Rise (Arctic Ocean) and Their Implications for the Paleoenvironment - Qingfeng Hua; Guanbao Li; Qingjie Zhou; Shujiang Li; Tengfei Xu; Baohua Liu; Hongxia Chen (Journal of Marine Science and Engineering, 2022)
Based on multibeam bathymetric data and high-resolution shallow sub-bottom profiles acquired during China’s 10th Arctic Scientific Expedition Cruise in 2019, a sediment wave field was found on the western slope of the Chukchi Rise, in the Arctic Ocean. This sediment wave field developed on the lower slope with water depths of between 1200 m and 1800 m and stretched 15 km in the downslope direction. It comprised several parallel sediment waves, with wavelengths ranging from 700 m to 3400 m and wave heights from 12 m to 70 m. In the vertical direction, well-stratified deposits, tens of meters thick, were affected by sediment waves, which exhibit asymmetric waveforms and upslope migration trends. The morphological and seismostratigraphic characteristics of the sediment waves suggested their genesis as a result of the interaction between the bottom current and seafloor morphology, which was also supported by hydrographical data adjacent to the sediment wave field. It was infered that this bottom current was related to the Arctic Circumpolar Boundary Current, which many researchers suggest flows through the study area.

Effects of shining pondweed (Potamogeton lucens) on bacterial communities in water and rhizosphere sediments in Nansi Lake, China - Nianxin Zhang; Mengmeng Wu; Yuying Che; Yong Kong; Fengyue Shu; Qingfeng Wang; Weilai Sha; Zhijin Gong; Jing Zhou (Environmental Science and Pollution Research, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Partitioning behaviors of zinc in eight coal-fired power plants with different fueled coals and air pollution control devices - Xian Zhou; Xinbin Feng; Xiangyang Bi; Xinyu Li; Qingfeng Wang; Shan Li; Tianrong He; Zhonggen Li (Environmental Science and Pollution Research, 2021)

Design, synthesis and biological evaluation of Schiff’s base derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Jian Shi; Yi Zhou; Keren Wang; Qinge Ma; Rongrui Wei; Qingfeng Li; Yiyang Zhao; Zhanpin Qiao; Shuang Liu; Yumin Leng; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2021)

Prevalence of HPV infections in surgical smoke exposed gynecologists - Xiaoli Hu; Qingfeng Zhou; Jian Yu; Jing Wang; Quanmei Tu; Xueqiong Zhu (International Archives of Occupational and Environmental Health, 2021)
Objectives Human papillomavirus (HPV) has been reported recently in surgical smoke generated by gynecological operations. The objective of this study was to investigate whether gynecologists who have performed electrosurgery including loop electrosurgical excision procedure (LEEP), are at risk of acquiring HPV DNA through surgical smoke. Methods A related questionnaire was designed and 700 gynecologist nasal swab samples were collected in 67 hospitals. In addition, the flow fluorescence hybridization technique was used to detect HPV DNA, and the Chi-square test was applied to analyze whether related risk factors including electrical surgery, were correlated with HPV infection in surgeons’ nasal epithelial cells. Results The HPV infection rate in the nasal epithelial cells of the participants who performed electrosurgery (8.96%, 42/469) or LEEP (10.11%, 36/356) was significantly higher than that in the remaining participants who did not perform electrosurgery (1.73%, 4/231) or LEEP (2.91%, 10/344), respectively. The most prevalent HPV genotype in the electrosurgery group was HPV16 (76.19%, 32/42). The HPV-positive rate was increased in the group that had a longer duration of electrosurgery ( P = 0.016). Additionally, the HPV detection rate was significantly lower in electrosurgery operators who used surgical mask (7.64%, 33/432) than in those who did not use protective masks (24.32%, 9/37). Furthermore, the N95 mask (0%, 0/196) significantly reduced the risk for HPV infection compared to that with the general mask (13.98%, 33/236, P < 0.001). Furthermore, 46 participants infected with HPV were followed-up for 3–24 months, and approximately 43.48% (20/46) and 100% (41/41) became negative for HPV DNA, respectively. Conclusions Gynecologists who performed electrosurgery including LEEP were at risk of acquiring HPV infection. Surgical masks, especially the N95 mask, significantly decreased the hazard of HPV transmission from surgical smoke.

Isolation and characterization of a recombinant Muscovy duck parvovirus circulating in Muscovy ducks in South China - Hanqin Shen; Jianfei Huang; Zhuanqiang Yan; Lijuan Yin; Qunhui Li; Qingfeng Zhou; Feng Chen (Archives of Virology, 2020)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Correction to: Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2020)

Distribution of water-stable aggregates under soil tillage practices in a black soil hillslope cropland in Northeast China - Lei Yan; Xuexin Jiang; Xiaonan Ji; Liting Zhou; Siying Li; Chen Chen; Peiye Li; Yuanchen Zhu; Tianhao Dong; Qingfeng Meng (Journal of Soils and Sediments, 2020)

Additional application of aluminum sulfate with different fertilizers ameliorates saline-sodic soil of Songnen Plain in Northeast China - Meng Zhou; Xiaobing Liu; Qingfeng Meng; Xiannan Zeng; Jizhou Zhang; Dawei Li; Jie Wang; Weiling Du; Xianfa Ma (Journal of Soils and Sediments, 2019)

Brucella abortus phosphoglyceromutase and dihydrodipicolinate reductase induce Th1 and Th2-related immune responses - Zhiqiang Li; Hui Zhang; Jinliang Zhang; Li Xi; Guangli Yang; Shuli Wang; Qingfeng Zhou; Xiaogen Zhang; Junbo Zhang (World Journal of Microbiology and Biotechnology, 2018)

Galangin inhibits hypertrophic scar formation via ALK5/Smad2/3 signaling pathway - Yifan Zhang; Shengzhou Shan; Jing Wang; Xinyu Cheng; Bo Yi; Jia Zhou; Qingfeng Li (Molecular and Cellular Biochemistry, 2016)

Distribution of carbon and nitrogen in water-stable aggregates and soil stability under long-term manure application in solonetzic soils of the Songnen plain, northeast China - Qingfeng Meng; Yuting Sun; Jing Zhao; Lianren Zhou; Xianfa Ma; Meng Zhou; Wei Gao; Guangcheng Wang (Journal of Soils and Sediments, 2014)

Diversity of Gene Cassette Promoter Variants of Class 1 Integrons in Uropathogenic Escherichia coli - Quhao Wei; Xiaofei Jiang; Min Li; Gang Li; Qingfeng Hu; Huoxiang Lu; Guoqiang Chen; Yonglie Zhou; Yuan Lu (Current Microbiology, 2013)

Cooperation among Numb, MDM2 and p53 in the development and progression of pancreatic cancer - Weiwei Sheng; Ming Dong; Jianping Zhou; Xin Li; Qingfeng Liu; Qi Dong; Feng Li (Cell and Tissue Research, 2013)

QTL mapping for the tocopherols at milk stage of kernel development in sweet corn - Faqiang Feng; Feng Deng; Peng Zhou; Jianbin Yan; Qingfeng Wang; Ruichun Yang; Xiaoqin Li (Euphytica, 2013)

Nitrogen impacts on atrazine-degrading Arthrobacter strain and bacterial community structure in soil microcosms - Xiaode Zhou; Qingfeng Wang; Zhao Wang; Shuguang Xie (Environmental Science and Pollution Research, 2013)

Transgenic mice with overexpression of mutated human optineurin(E50K) in the retina - Qingfeng Meng; Zheng Xiao; Huiping Yuan; Fei Xue; Yuanmao Zhu; Xinrong Zhou; Binbin Yang; Jingbo Sun; Bo Meng; Xian Sun; Fang Cheng (Molecular Biology Reports, 2012)

Analysis of Nitrosamines Migration from Condoms in the Chinese Market Using a Proper Migration Experiment - Di Feng; Qingfeng Zhou; Xuelian Cheng; Jiedong Wang; Quanli Yang (Bulletin of Environmental Contamination and Toxicology, 2010)

An improved reverse transcription loop-mediated isothermal amplification assay for sensitive and specific detection of Newcastle disease virus - Qiang Li; Chunyi Xue; Jianping Qin; Qingfeng Zhou; Feng Chen; Yingzuo Bi; Yongchang Cao (Archives of Virology, 2009)

Cloning and Expression of a Clamworm Antimicrobial Peptide Perinerin in Pichia pastoris - Qingfeng Zhou; Mingyue Li; Tao Xi (Current Microbiology, 2009)